FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE DENGAN VARIABEL KONTROL FIRM SIZE - Ng, Gabriela Jesslyn; Yanti, Yanti (Jurnal Paradigma Akuntansi, 2023)
The objective of this study is to determine the effect of leverage, liquidity, profitability and sales growth towards the firm's value. This research uses secondary data from manufacturing companies that is listed on the Indonesian Stock Exchange during the period of 2016-2019. The sample is selected using purposive sampling and amounted to 50 companies. The data is processed by using SPSS 25 and Eviews 12. Outputs obtained from this study indicates that leverage and profitability has a positive and significant influence towards firm value. Liquidity has a positive but not significant influence towards firm value. Sales growth has a negative and significant influence on firm value. Control variable firm size has a negative and significant influence on firm value.